AYURVEDA PERSPECTIVE ON MOOTRASHMARI AND ITS MANAGEMENT: AN LITERATURE BASED REVIEW - Patel, Diwakar; Kulshrestha, Deepak (Journal of Drug Delivery and Therapeutics, 2018)
The formation of stone is one of the common problems of urinary system and as per modern science only few medicines are available for such condition along with surgery. It is second most common disease of urinary tract with high recurrence rate. The common symptoms of ureter culculi are pain, haematuria, burning micturiton, dysurea, tenderness and sometimes fever. Ayurveda described Mootrashmari as urinary calculus disease of Mutravaha Srotas and considered as Asthamahagada. Ayurveda described various treatment approaches for the management of disease; use of herbs, ayurveda formulation and Kshara, etc. this article presented summarative review on Mootrashmari.Keywords: Ayurveda, Ashmari, Mutravaha Srotas, Mootrashmari